2017
DOI: 10.2174/1389557516666161004162133
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis: A Treasure Trove or Pandora's Box?

Abstract: We summarize our current knowledge on the recreational use of cannabis with respect to the modes of consumption, short-term effects, chronic health consequences and cannabis use disorder. Next, we overview the molecular targets of a dozen major and minor bioactive cannabinoids in the body. This helps us introduce the endocannabinoid system in an unprecedented detail: its up-todate molecular biology, pharmacology, physiology and medical significance, and beyond. In conclusion, we offer an unbiased survey about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(132 citation statements)
references
References 897 publications
(1,547 reference statements)
1
127
1
3
Order By: Relevance
“…The exact pharmacological identification of the receptor influenced by the cannabinoid compound used in this work is outside its objective. However, there is evidence that supports the possibility of the presently described actions of WIN 55,212‐2 being mediated through CB 1 R. WIN 55‐212,2 is one of the most commonly used cannabinomimetics to study the role of the CB 1 R and the CB 2 R (Solymosi and Köfalvi ), showing similar preference for activating both receptors (Pertwee et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The exact pharmacological identification of the receptor influenced by the cannabinoid compound used in this work is outside its objective. However, there is evidence that supports the possibility of the presently described actions of WIN 55,212‐2 being mediated through CB 1 R. WIN 55‐212,2 is one of the most commonly used cannabinomimetics to study the role of the CB 1 R and the CB 2 R (Solymosi and Köfalvi ), showing similar preference for activating both receptors (Pertwee et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Pertwee et al . ; Solymosi and Köfalvi ). We previously showed that the CB 1 R selective antagonist (AM 251) abolished the impact of acute WIN 55,212‐2 administration on recognition memory, which was evaluated with the same NORT paradigm and using mice of the same age as used in this study (Mouro et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than a 100 pCB have been identified, of which the psychotropic (–)- trans -Δ 9 -tetrahydrocannabidiol (THC) and the nonpsychotropic (–)-cannabidiol (CBD) are the best studied [14-16]. THC and CBD mediate a broad spectrum of biological actions including analgesic, antiemetic, and anti-inflammatory effects [12-14].…”
Section: Cannabinoids and The Endocannabinoid Systemmentioning
confidence: 99%
“…THC and CBD mediate a broad spectrum of biological actions including analgesic, antiemetic, and anti-inflammatory effects [12-14]. …”
Section: Cannabinoids and The Endocannabinoid Systemmentioning
confidence: 99%